Common Etiologies of Neonatal Pleural Effusion - Yueh-Ting Shih; Pen-Hua Su; Jia-Yuh Chen; Inn-Chi Lee; Jui-Ming Hu; Hua-Pin Chang (Elsevier, 2011)
Pleural effusion is rare and includes several disease entities in the neonatal period. The aim of this study was to investigate the etiology, management, and outcome of neonatal pleural effusions. Methods: We retrospectively collected all neonates who were admitted to the neonatal intensive care unit of Chung Shan Medical University Hospital, Taichung, Taiwan, with discharge diagnosis of pleural effusion, chylothorax, hydrothorax, hemothorax, and empyema, from January 1999 to December 2009. The characteristics, etiology, management, and outcome were analyzed. Results: There were 21 patients identified, 16 males (76%) and 5 females (24%). Eight patients (38%) had primary and 13 patients (62%) had secondary etiologies. The etiologies included four parapneumonic effusions or empyema (19%); nine chylothorax (42.8%) with four congenital and five iatrogenic after thoracic surgery; three percutaneously inserted central venous catheter extravasation (14%); one umbilical venous catheter extravasation (4.7%); three hydrops fetalis (14%); and one congestive heart failure (4.7%). Fifteen patients (71%) needed chest tube placement. Conservative management with complete cessation of enteral feedings and use of total parenteral nutrition followed with infant formula containing medium-chain triglyceride was successful in six of the patients (67%) with chylothorax. There were two patients (22%) with chylothorax who received somatostatin administration; one was successful and the other one failed. Thoracic duct ligation was performed uneventfully in two patients with acquired chylothorax. There were three mortalities (14.3%) in this study, which were related to causes other than pleural effusion. Conclusions: Pleural effusions in the neonatal stage may result from chylothorax, hydrops fetalis, extravasation of percutaneously inserted central venous catheter, parapneumonic effusion, congestive heart failure, or other less frequently occurring conditions. Diagnostic chest tap is required for subsequent management. Good outcome is the rule except in hydrops fetalis, which carries high mortality rate.